Development of breathable Janus superhydrophobic polyester fabrics using alkaline hydrolysis and blade coating. Issue 6 (March 2019) - Youn, Seonyoung; Hee Park, Chung
Alkaline hydrolysis is a common finishing method that is used to give polyester (polyethylene terephthalate, PET) a more natural touch and improved luster via chemical or physical changes in the fibers. However, its potential as a tool for surface modification in the development of single-sided superhydrophobic materials has not been studied yet. In this research, Janus superhydrophobic PET fabrics with asymmetric wetting properties (one side of the PET surface was rendered superhydrophobic while the other side was simply hydrophobic) were fabricated in two steps. Fine roughness was first achieved on the surface of PET fabrics by alkaline hydrolysis. Subsequently, optimized foam-coating emulsions were applied on only one surface of the alkaline-hydrolyzed PET. Alkaline treatment time, solution temperature, and viscosity of the foam-coating emulsions were varied to find optimal conditions in terms of structural changes, mechanical properties, superhydrophobicity, and absorption ability. The specimen treated with an aqueous solution of 8% sodium hydroxide at 70℃ for 60 min and coated with the mixture of the fluoro-emulsion and thickener in the volume ratio of 40:2 was determined to be the optimal conditions for the Janus superhydrophobic property. This sample showed a contact angle of 162.8° and a shedding angle of 5.6° on one side, whereas it completely permitted the percolation of water drops on the other side within 109 s. The mechanical properties of the developed Janus PET under the optimal conditions did not decrease significantly; its weight and tensile strength were found to have decreased by 3.3% and 19.2%, respectively. Furthermore, the single-sided superhydrophobic specimen demonstrated higher moisture transmissibility than the double-sided coated PET under the same alkaline treatment conditions. The method developed herein eliminates the requirement for an additional process to deliver nanoscale surface roughness and has the potential to produce waterproof–breathable PET fabrics for outdoor clothing.